Bioreactor Co-Composting Of Sewage Sludge and Restaurant Waste - Abdul Razak, Abdul Rahman (2003)

(untitled)
Composting is an environmental-friendly method to tackle the disposal problem of sewage sludges and municipal solid waste. With appropriate nutrients, porosity, density and moisture content during composting, pathogens such as Salmonella typhi, Escherichia coli etc. will be destroyed and the organic matter will be stabilized producing a compost product that can contribute directly to soil fertility and conditioning. Composting process system has been modernized from the heap or windrow system to the reactor system, which is a comparatively fast process. A 200 liters rotating drum bioreactor/composter was designed, fabricated and used in this cocomposting study. This bioreactor was designed in Universiti Putra Malaysia and was fabricated by Amsea Environment Sdn. Bhd. Three different types of dewatered sewage sludges, i.e. septic tank, oxidation pond and activated sewage sludges were successfully co-composted with municipal solid waste in a two-stage process. The physicochemical and biological characteristics of these municipal solid waste (restaurant waste) and sewage sludges were measured before being used as raw materials for the co-composting process. For the bioreactor composting, the raw materials were fermented for 7 days inside the 200 liters bioreactor before being matured outside the bioreactor in a windrow pile until fully matured and ready to be used. A 2:1 (w/w) ratio of municipal solid waste and sewage sludge was found to give the best initial C/N ratio for the composting process. The carbon content decreased and the nitrogen content increased towards the end of the composting process, which resulted in the reduction of C/N ratio during the composting process to below 20. The low C/N ratio of the final compost product was very important as the indicator of compost maturity and stability. The breakdown of organic materials inside the bioreactor did not increase the temperature to the thermophilic range (50-60°C), where breakdown of organic matter by microorganisms is at the optimum rate. In order to overcome the temperature problem, heated air was supplied to the bioreactor, increasing the temperature of the composting process. Shredded garden waste was added as bulking agent. Bioreactor co-composting took around 40-45 days to produce matured compost. The characteristics of the sewage sludge compost products were almost similar compared to commercial compost available in the local market and also complied with the United States Environmental Protection Agency (USEPA) standard. By using bioreactor system the compost products were improved based on nutrient contents and duration of composting process. The planting out performance of spinach with the research compost showed satisfactory results.